Hash‐One: a lightweight cryptographic hash function. Issue 5 (1st September 2016) - Megha Mukundan, Puliparambil; Manayankath, Sindhu; Srinivasan, Chungath; Sethumadhavan, Madathil
Abstract : The increased demand for lightweight applications has triggered the need for appropriate security mechanisms in them. Lightweight cryptographic hash functions are among the major responses toward such a requirement. The authors thus have a handful of such hash functions such as QUARK, PHOTON, SPONGENT and GLUON introduced already. The cryptanalysis of these hash functions is crucial in analysing their strength and often calls for improvement in designs. Their performance, are also to be taken care of, in terms of both software and hardware implementations. Here, they propose a lightweight hash function with reduced complexity in terms of hardware implementation, capable of achieving standard security. It uses sponge construction with permutation function involving the update of two non‐linear feedback shift registers. Thus, in terms of sponge capacity it provides at least 80 bit security against generic attacks which is acceptable currently.